"El problema" de Soto Hall o las aporías del nacionalismo oligárquico - Quesada Soto, Alvaro (1994)
“El problema” a book written by the Guatemalan Máximo Soto Hall, should be considered the first Costa Rican novel. This article discusses whether it should be considered a nationalist or cosmopolitan one, and analyzes the characteristics of oligarchical nation discourse.